Strukturalne uwarunkowania produktywności pracy w Unii Europejskiej w Latach 1994-2004 - Jahn, Joanna (The structural conditions of labour in the European Union in years 1994-2004, 2006)
The article concerning problems of changing the productivity of labour in the European Union. There are appointed structural conditions of labour productivity in the European Union and Member Countries. The considerations apply for years 1994-2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 200-208